Respuesta :

1.
f(x) = x
g(x) = x + 3

For each x value you use in f(x) and g(x), the corresponding y value in g(x) is always 3 more than in f(x). If each y-coordinate is 3 more, that means the graph is shifted 3 units up. The graph of f(x) is shifted 3 units up to create the graph of g(x).

2.
The first term is -0.5.
Then each term goes up by 0.25.

1st term: -0.5
2nd term: -0.5 + 0.25 = -0.5 + 0.25(1)
3rd term: -0.5 + 0.25 + 0.25 = -0.5 + 0.25(2)
4th term: -0.5 + 0.25 + 0.25 + 0.25 = -0.5 + 0.25(3)
nth term: -0.5 + 0.25(n - 1)

-0.5 + 0.25(n - 1) = -0.5 + 0.25n - 0.25 = -0.75 + 0.25n = 0.25n - 0.75

Answer is C.